2022
DOI: 10.3389/fmicb.2022.1042846
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic supplementation during pregnancy alters gut microbial networks of pregnant women and infants

Abstract: BackgroundProbiotic supplementation has been popular and widespread, yet we still lack a comprehensive understanding of how probiotic supplementation during pregnancy affects the gut microbial networks of pregnant women and infants. In this study, we firstly used network analysis to compare the gut microbiota of pregnant women with and without probiotic supplementation, as well as their infants.MethodsThirty-one pairs of healthy pregnant women and infants were recruited and randomly divided into the probiotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…As the main determinants of population structure and dynamics, these interactions are essential for the formation of microbial communities [ 50 ]. According to previous studies, a higher number of links and an average degree indicate that the networks are more complex, and networks with more complexity are typically more stable [ 51 , 52 ]. According to our findings, the numbers of links and the average degree of both GT1–2 and PT1–2 were higher than those of the control, which implies that both disinfectants may be advantageous to the complexity of the BSFL gut microbiota ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the main determinants of population structure and dynamics, these interactions are essential for the formation of microbial communities [ 50 ]. According to previous studies, a higher number of links and an average degree indicate that the networks are more complex, and networks with more complexity are typically more stable [ 51 , 52 ]. According to our findings, the numbers of links and the average degree of both GT1–2 and PT1–2 were higher than those of the control, which implies that both disinfectants may be advantageous to the complexity of the BSFL gut microbiota ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the results also indicate an increase in the percentage of positive links in GT1–2 and PT1–2 in comparison to the control. Cooperation may be a key mode of interaction between bacteria in a relatively healthy gut [ 52 ]. Although digestion could be influenced by many factors, such as the composition of manures and dominant species, our findings suggest that BSFL fed swine manures treated with both disinfectants may have a more complex and cooperative microbial community at the very least.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is scarce evidence that this intervention determines sustained colonization or can significantly influence the overall diversity of the infant microbiome [51][52][53]. While some studies report a higher abundance of supplemented species at the time of intervention [52][53][54][55][56][57], other research indicated no notable changes in the abundance of species added through supplementation following the discontinuation of the probiotic treatment [58][59][60][61]. A recent metanalysis of seven studies affirms that supplementing mothers with probiotics during pregnancy and breastfeeding leads to the infant's gut being colonized by the species provided [51].…”
Section: Probiotics and Prebiotics During Pregnancy And Lactationmentioning
confidence: 99%
“… Cephalosporin 23 Respiratory tract, urinary tract and skin infections, gonorrhea. Carbapenems 24 Gram-negative bacterial infections of the urinary tract, kidney, gastrointestinal tract, respiratory tract, and urogenital and pelvic area. Azithromycin, erythromycin 25 Macrolides Respiratory, intestine, gynecological, urogenital and skin infections, chlamydia infections and syphilis.…”
Section: Antibiotics In Mother-infant Dyadsmentioning
confidence: 99%
“…On the other hand, infants at high risk of developing allergies are also recommended to receive probiotic supplementation 154 . There is no evidence that taking probiotics or prebiotics during pregnancy causes infant and maternal adverse pregnancy outcomes 22 , but significantly modulates the maternal gut microbiota and immune status 23 , 24 .…”
Section: How Can We Reduce Antibiotic Resistance In Mother-infant Dyads?mentioning
confidence: 99%